2009
DOI: 10.1007/s12272-009-1601-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of saponin fraction from Codonopsis lanceolata on immune cell-mediated inflammatory responses

Abstract: Saponin components are known to be pharmaceutically, cosmetically and nutraceutically valuable principles found in various herbal medicine. In this study, we evaluated the inhibitory role of saponin fraction (SF), prepared from C. lanceolata, an ethnopharmacologically famous plant, on various inflammatory responses managed by monocytes, macrophages, lymphocytes and mast cells. SF clearly suppressed the release of nitric oxide (NO) and tumor necrosis factor (TNF)-alpha, but not prostaglandin E(2) (PGE(2)). Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…This plant is widely used to treat several inflammatory diseases, such as asthma, tonsillitis, and pharyngitis (Yongxu and Jicheng, 2008; Byeon et al ., 2009). The compounds from this plant are saponins, alkaloids, tannins, steroids, and polysaccharides (Ushijima et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This plant is widely used to treat several inflammatory diseases, such as asthma, tonsillitis, and pharyngitis (Yongxu and Jicheng, 2008; Byeon et al ., 2009). The compounds from this plant are saponins, alkaloids, tannins, steroids, and polysaccharides (Ushijima et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2B and C), suggesting that the activation and migration of mast cells may be a target immunopharmacology of CBBF. To show whether CBBF directly modulated histamine release from activated mast cells, we treated RBL-2H3 cells with DNP-labeled IgE (Byeon et al, 2009), and their degranulation events were continuously followed. As Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The RBL-2H3 cells were grown in DMEM supplemented with 10% FBS in a 5%-CO 2 -containing atmosphere as described previously (Byeon et al, 2009). RBL-2H3 cells (2 × 10 5 cells/well) pretreated with CBBF or azelastine (Sigma, St Louis, MO) were sensitized with 1 g/ml anti-DNP IgE for 60 min at 37 • C. IgE-sensitized cells were washed with PBS.…”
Section: Hexosaminidase Secretion Assaymentioning
confidence: 99%
“…In real, many studies about anti-inflammatory activity by KRG-TS have been reported (Byeon et al, 2009;Park and Cho, 2009;Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%